2018
DOI: 10.1007/s11548-018-1836-1
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based detection of motion artifacts in probe-based confocal laser endomicroscopy images

Abstract: Over traditional machine learning approaches with state-of-the-art features, we achieved significantly improved overall performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 36 publications
0
24
0
3
Order By: Relevance
“…Convolutional neural networks are also very effective for other image classification tasks. In [70] they are employed to automatically detect images containing motion artifacts in confocal laser-endoscopy images.…”
Section: Image Detection and Recognitionmentioning
confidence: 99%
“…Convolutional neural networks are also very effective for other image classification tasks. In [70] they are employed to automatically detect images containing motion artifacts in confocal laser-endoscopy images.…”
Section: Image Detection and Recognitionmentioning
confidence: 99%
“…Eine wichtige Voraussetzung für eine korrekte Interpretation ist die Bildqualität. Mit den derzeit verfügbaren Methoden sind die CLE-Aufnahmen häufig durch Rausch-oder Bewegungsartefakte verfälscht [36][37][38][39].…”
Section: Computergestützte Auswertungunclassified
“…Daher unterscheiden sich die verschiedenen Geräte in ihrer Anfälligkeit für Artefakte. Bildverarbeitungssysteme haben das Potenzial, alle wichtigen Artefakt-Typen zu erkennen und zu eliminieren [38,39]. Sie ermöglichen nicht nur die automatische Klassifizierung der Befunde, sondern erhöhen auch die Qualität der Bilder, um die einfache klinische Anwendung zu realisieren.…”
Section: Computergestützte Auswertungunclassified
“…Although this technique's potential has been recognized over the years by a few groups, it has not yet achieved a broad clinical application. A further possibility to objectivize CLE findings is utilizing automatic classification [26]. Aubreville et al showed that an approach based on transfer learning from intermediate endpoints within a pre-trained inception v3 network with preprocessing could reach an overall 94.8% accuracy, significantly improving overall performance over the traditional state of the art feature-based machine learning approaches [26].…”
Section: Discussionmentioning
confidence: 99%